Multi-method solutions to the problem of dating early trackways and associated colluvial sequences. (August 2020) - Bell, M.; Black, S.; Maslin, S.; Toms, P.
Abstract: Trackways show how sites linked together as parts of living landscapes. Prehistoric trackways, especially hollow ways, are often regarded as undatable. Where trackways are bounded by early fields, colluvial sediment accumulations can provide dating evidence. The case study of a trackway at Lyminge, Kent, UK is dated using a multi-method strategy, including optically stimulated luminescence, uranium series, molluscs and artefacts, indicating it is of late prehistoric or Romano-British origin. This demonstrates that a combination of methods can reveal secure chronologies for trackways, lynchets and other colluvial sediments such as valley fills in many landscapes.